2020
DOI: 10.1186/s40545-020-00245-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sanction and healthcare system reform on the healthcare performance and pharmaceutical market in Iran; 2001-2016

Abstract: Background: Iranian government has introduced multiple healthcare system reforms during the last 30 years aiming at improving accessibility and affordability of care. Pharmaceutical products are one of the major sources of financial burden on the healthcare system. The healthcare system and pharmaceutical sector have been balanced out by the partially counteracting effects of the HSEP (Health sector evolution plan) and the imposed sanctions. Methods: This research investigates the healthcare system performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“… 59 , 66 , 68 , 70 , 82 We also found that during sanctions periods, industrial production fell, 40 , 54 national industries were weakened or bankrupted, 13 , 40 , 46 , 48 , 60 , 75 , 82 per capital gross national product and gross domestic product declined substantially, 13 , 42 , 44 , 46 , 47 , 52 , 75 , 83 and recessions developed. 75 These economic disruptions severely weakened health and social systems, 13 , 47 , 54 , 60 impacted social security spending, 13 , 60 reduced resources for health care services, 13 , 47 , 54 , 60 , 66 , 75 , 82 prevented governments from responding to public health emergencies, 47 led to shortages of medicines and other medical supplies, 47 , 50 , 54 , 70 , 73 , 83 and resulted in extensive rationing of food and medicines. …”
Section: Indirect Impact Of Sanctions On Healthmentioning
confidence: 60%
See 4 more Smart Citations
“… 59 , 66 , 68 , 70 , 82 We also found that during sanctions periods, industrial production fell, 40 , 54 national industries were weakened or bankrupted, 13 , 40 , 46 , 48 , 60 , 75 , 82 per capital gross national product and gross domestic product declined substantially, 13 , 42 , 44 , 46 , 47 , 52 , 75 , 83 and recessions developed. 75 These economic disruptions severely weakened health and social systems, 13 , 47 , 54 , 60 impacted social security spending, 13 , 60 reduced resources for health care services, 13 , 47 , 54 , 60 , 66 , 75 , 82 prevented governments from responding to public health emergencies, 47 led to shortages of medicines and other medical supplies, 47 , 50 , 54 , 70 , 73 , 83 and resulted in extensive rationing of food and medicines. …”
Section: Indirect Impact Of Sanctions On Healthmentioning
confidence: 60%
“…13,47,59,68,70,80,82 A disturbing finding was articles reporting that under U.S. sanctions, even non-U.S. companies refused to sell supplies to sanctioned countries to avoid U.S. penalties. 59,66,68,70,82 We also found that during sanctions periods, industrial production fell, 40,54 national industries were weakened or bankrupted, 13,40,46,48,60,75,82 per capital gross national product and gross domestic product declined substantially, 13,42,44,46,47,52,75,83 and recessions developed. 75 These economic disruptions severely weakened health and social systems, 13,47,54,60 impacted social security spending, 13,60 reduced resources for health care services, 13,47,54,60,66,75,82 prevented governments from responding to public health emergencies, 47 led to shortages of medicines and other medical supplies, 47,…”
Section: Economic Effectsmentioning
confidence: 73%
See 3 more Smart Citations